0737 Parent-reported Snoring Compared To Objectively Measured Snoring As Predictors Of Pediatric Sleep Disordered Breathing (SDB). (12th April 2019) - Schwartz, Nat; Guo, Na; Li, Xiaoyu; Owens, Judith; Gold, Diane; Phipatanakul, Wanda; Redline, Susan
Abstract: Introduction: Parent-reported snoring is commonly used to assess pediatric SDB risk. However, reports have identified variable associations between parent-reported snoring and polysomnography findings. Since sound sensors may improve snoring measurement, we assessed: 1) The correlation between parent-reported and objective snoring; 2) How each snoring measure predicted SDB. Methods: The sample included 42 children of an ongoing cohort study of pediatric SDB in Boston, Environmental Assessment of Sleep in Youth. Participants underwent assessments including an in-home sleep apnea study (WatchPAT 200U; Itamar Medical). The apnea-hypopnea index (AHI) was estimated from peripheral arterial tonometry and oxygen desaturation (3%), and snoring was captured by the device's acoustic decibel detector. Objective snoring was measured by percent total sleep time (TST) with snoring over three thresholds (40/45/50 dB). Parents reported child snoring using three questions regarding occurrence, loudness and frequency of snoring over the last month. Mild and moderate SDB were defined as AHI ≥2 and ≥5, respectively. Results: This sample included 62% boys and 68% ethnic minorities and had an average age of 10.0 years (6-12). Mild and moderate SDB were identified in 71% and 12% of the sample, respectively. Snoring 3-7 times per week was reported for 24% of children. The median percent TST with snoring over 50 dB was 3.4% (IQR: 2.8-4.0). Parent-reported snoring had moderate correlations with snoring over 50dB (Spearman's correlation: 0.31-0.43, p <0.05). None of the parent-reported snoring measures predicted SDB (C-statistics: 0.54-0.59). Objective measures of snoring weren't associated with mild SDB but snoring over 50dB was predictive of moderate SDB ( p = 0.03, C-statistic: 0.81). Under the optimal cutoff of snoring over 50dB ≥ 2.8% TST, the sensitivity and specificity for moderate SDB were 0.80 and 0.84, respectively. Conclusion: These analyses suggest that 1) Parent-reported snoring nly modestly correlates with objective snoring; 2) Percent TST with snoring over 50 dB predicts moderate but not mild SDB; 3) Parent-reported snoring is not associated with SDB. Assessment of SDB risk may benefit from objective corroboration of parent-reported snoring. Support (If Any): NIH R01HL137912